Performance Evaluation of a Solar Humidification – Dehumidification Desalination Unit (The International Journal of Engineering & Information Technology (IJEIT), 2015)
This paper is to investigate the use of solarenergy in desalination by humidification and dehumid-ification process (HD). Here, a proposal for the desalinationunit has been come out with cylindrical shape containing the evaporator in the middle and surrounded by the condenser.The hot feed water coming from the solar thermal system issprayed at the top of the evaporator where the air flowsfrom the bottom. In the evaporator the air is humidified until it gets out saturated, then introduced to the condenser,where it is dehumidified to obtain the fresh water andcirculated back to the evaporator. Practically there aremany parameters influence on the performance of thisdesalination unit, which are environmental, design and operational. In the current study these parameters are takenin consideration to formulate mathematical models whichgovern the performance of the main components of this unit,which are the evaporator, the condenser and the solarthermal system. The deduced mathematical models have been interpreted in many programs in visual basic languageas a computer software. This software contains many pageswhich help in introducing and analyzing the most influentialparameters. In this case many operational parameters havebeen studied such as feed water temperature, mass flow rate and salinity, in addition to cooling water mass flow rate andinlet temperature, as well as quantity of solar irradiancewith others. At these inputs many outputs have beenobtained which are related to the performance of thedesalination unit such as fresh water productivity, energy consumption, humidifier volume, recovery ratio and gainoutput ratio.